Pengaruh Manajemen Pengelolaan Pamsimas Terhadap Kepuasan Pelanggan Desa Gempolrejo Dusun Sumberjo Kecamatan Tunjungan KAB. Blora - Saryono Saryono; Amelia Anwar (Jurnal Manajemen Riset Inovasi, 2024)
Pamsimas is a program implemented by the government to help the community in providing drinking water and overcoming difficulties in getting clean water. This research aims to determine the influence of Pamsimas Management on Customer Satisfaction of Community-Based Drinking Water (PAMSIMAS). The Pamsimas program is one of the programs implemented by the Indonesian Government. The aim of this research is to find out about the "Influence of Pamsimas Management on Customer Satisfaction in Gempolrejo Village, Sumberjo Hamlet, Tunjungan District, Blora Regency" to see how the Pamsimas program is in terms of its management, researchers want to know what strategies management uses to overcome water problems during the dry season. and the level of community satisfaction. Researchers use data collection techniques with techniques; interviews, observation, documentation and using qualitative data analysis techniques. Indicators of the success of the Pamsimas program are: Fulfillment of clean water needs every day and a good level of community satisfaction. Research results related to the success and strategy of providing community-based drinking water in Gempolrejo village, Sumberjo hamlet. The program is said to be successful because Porgam's objectives have been achieved, but there are still obstacles in several aspects, such as a lack of water during long dry periods and a lack of community satisfaction. In this case, support from the government and society is really needed.